REPRESENTASI SIMBOL KOMUNIKASI NON VERBAL JAMAAH AN-NADZIR DALAM MENYEBARLUASKAN IDEOLOGI ISLAM DI KABUPATEN GOWA - Imam Mukti; Ismail Ismail (KAREBA : Jurnal Ilmu Komunikasi, 2020)
The existence of Jamaah An-Nadzir has given its own colour to the development of Islamic da'wah in Indonesia, especially in Gowa district. This study aims to identify, analyze, and explain in depth the representation of Jamaah An-Nadzir non-verbal communication symbols and the An-Nadzir congregation's da'wah method by placing all the signs used by the An-Nadzir congregation. This research method is descriptive qualitative using the semiotic analysis model of Roland Barthes. This method is used because the researcher wants to learn in depth about the meaning of the denotation signs, connotations, myths and ideologies that exist in the An-Nadzir congregation. Data collection was carried out through observation and in-depth interviews with several figures and members of Jamaah An-Nadzir. The results showed that An-Nadzir's symbols tended to represent the other side of Islamic ideology. Myths and ideology of the symbols used by An-Nadzir such as robes, turban, beard and long hair that are braided as a whole are the culture and Sunnah of the Prophet SAW. Sociologically and philosophically, the way of worship and the communication process that occurs in the community is an exemplary concept.